Does Trade Exposure Explain Anti-Globalization Votes? - Antoine Bouët; Anthony Edo; Charlotte Emlinger (Institute of Labor Economics (IZA), 2024)
We investigate the local effects of trade exposure and immigration on voting behavior in France from 1988 to 2022. We use the content of each candidate's manifesto to construct an anti-globalization voting index for each French presidential election. This index shows a significant increase in the anti-globalization positions of candidates, and a growing anti-globalization vote beyond the far right. We show that increasing local exposure to import competition and immigration increases anti-globalization votes, while increasing export exposure reduces them. We also find that imports have different effects depending on the products imported. While exposure to imports of final goods increases anti-globalization voting, exposure to imports of intermediate goods reduces it.
Keywords: D72; F6; 330; voting; trade; immigration; political economy